Implementation of the Pomodoro Method to Improve Student Learning Outcomes in Natural and Social Sciences Learning at MIN 20 Banjar - Pratama, Wahyu Putra Marga Aji; Astuti, Welly; Nahrowi, Wawi; Jannah, Wardatul; Utami, Wahyu (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to analyze the application of the Podomoro method in improving the learning outcomes of Natural and Social Sciences (IPAS) on the material of Hindu-Buddhist Kingdoms in the Archipelago. The subjects of the study were fourth grade students of MIN 20 Banjar in semester 2. The Podomoro method, which prioritizes learning with work and rest time division techniques, is applied to improve students' concentration and understanding of historical material. This study uses a quantitative method with an experimental design. Data were collected through learning outcome tests before and after the application of the Podomoro method, as well as observations and interviews with students and teachers. The results showed a significant increase in student learning outcomes after the application of the Podomoro method. Students became more focused, motivated, and found it easier to understand the concept of Hindu-Buddhist kingdoms compared to conventional learning methods. Thus, the Podomoro method can be used as an alternative in IPAS learning, especially in history material, to improve the effectiveness of learning and student learning outcomes. This study recommends the use of this method more widely in other subjects to improve the quality of learning at the elementary school level.